Propuesta de un plan de marketing digital en la empresa Alfalum decoraciones en Santa Marta - Caicedo Ossa, Javier Andrés (Universidad Antonio Nariño, 2024)
This document intends to display a proposal for a digital marketing plan for the company ALFALUM in order to design a commercial action scheme with the purpose of positioning the brand in the future, in addition to optimizing the recognition of the company's value elements. among the current customer base, simplifying the interaction. In the present investigation, a cross-sectional cuantitative .- exploratory recognition scheme is implemented under a quasi-experimental approach, starting from the recognition of the current client of the company in order to understand their problems and needs. The recognition method is descriptive, since a set of procedures and logical processes are used based on a primary study through a measurement survey, and based on these results, an intervention scheme is formulated for the design of a management plan. digital marketing that allows to achieve an optimal positioning model in the long term.